Why Are Losses Less Persistent Than Profits? Curtailments vs. Conservatism - Lawrence, Alastair; Sloan, Richard; Sun, Estelle (Management Science, 2018)
It is well documented that losses are less persistent than profits and that stock prices anticipate the lower persistence of losses. Yet the underlying explanation for these results is unclear. One explanation lies in the abandonment option, whereby firms with losses are more likely to curtail operations (e.g., Hayn [Hayn C (1995) The information content of losses. J. Accounting Econom. 20(2):125–153]). Another explanation involves timely loss recognition stemming from conservative accounting (e.g., Basu [Basu S (1997) The conservatism principle and the asymmetric timeliness of earnings. J. Accounting Econom. 24(1):3–37]). We provide direct evidence that curtailments are an important factor contributing to the lower persistence of losses. An implication of our results is that popular measures of conservatism, such as the measure proposed by Basu, also reflect curtailments. This paper was accepted by Suraj Srinivasan, accounting.